Pengembangan produk UMKM risol Dangke untuk pemberdayaan ekonomi masyarakat Desa Lebang - Muh. Basyir Usman; Ahmad; Nurul Fatwa Jamaluddin; Mazlan Ahmad; Juliati; Mutmainna, Inah; Muh. Khaerul Fajran; Yanti; Mirjayadi I; Cahaya Amaliah Darwis (P3HKI - Universitas Muhammadiyah Parepare, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in enhancing local economies, including in Lebang Village, Enrekang Regency. Fluctuating dangke sales lead to product spoilage and reduced community income. This service activity aims to develop an innovative